2014
DOI: 10.1083/jcb.2075oia222
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 enhances skeletal muscle regeneration through MT1-mediated oxidative stress protection in a mouse model of dystrophinopathy

Abstract: The Polycomb group (PcG) protein Bmi1 is an essential epigenetic regulator of stem cell function during normal development and in adult organ systems. We show that mild upregulation of Bmi1 expression in the adult stem cells of the skeletal muscle leads to a remarkable improvement of muscle function in a mouse model of Duchenne muscular dystrophy. The molecular mechanism underlying enhanced physiological function of Bmi1 depends on the injury context and it is mediated by metallothionein 1 (MT1)-driven modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Our group has shown that Bmi1 overexpression in the satellite cells increases the Pax7 + /MyoD − proportion of the satellite cells in vitro , without impairing their differentiation potential . We also showed that mild overexpression of Bmi1 specifically in the satellite cells enhances the muscle strength of mdx mice after challenge with treadmill exercise for 6 weeks (Figure ).…”
Section: Modulation Of Pcg Gene Expression As a Tool To Enhance Musclmentioning
confidence: 63%
See 4 more Smart Citations
“…Our group has shown that Bmi1 overexpression in the satellite cells increases the Pax7 + /MyoD − proportion of the satellite cells in vitro , without impairing their differentiation potential . We also showed that mild overexpression of Bmi1 specifically in the satellite cells enhances the muscle strength of mdx mice after challenge with treadmill exercise for 6 weeks (Figure ).…”
Section: Modulation Of Pcg Gene Expression As a Tool To Enhance Musclmentioning
confidence: 63%
“…Our group has shown that Bmi1 overexpression in the satellite cells increases the Pax7 + /MyoD − proportion of the satellite cells in vitro , without impairing their differentiation potential . We also showed that mild overexpression of Bmi1 specifically in the satellite cells enhances the muscle strength of mdx mice after challenge with treadmill exercise for 6 weeks (Figure ). Importantly, a similar experimental approach did not lead to a significant improvement of muscle strength in non‐dystrophic mice upon acute traumatic muscle injury, highlighting the context‐specificity of the efficacy of Bmi1 modulation in muscle regeneration.…”
Section: Modulation Of Pcg Gene Expression As a Tool To Enhance Musclmentioning
confidence: 63%
See 3 more Smart Citations